2020
DOI: 10.3866/pku.whxb201907006
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning Model for Predicting the Rate Constant of ProteinLigand Dissociation

Abstract: An increasing number of recent studies have shown that the binding kinetics of a drug molecule to its target correlates strongly with its efficacy in vivo. Therefore, ligand optimization oriented to improved binding kinetics provides new ideas for rational drug design. Currently, ligand binding kinetics is modeled mainly through extensive molecular dynamics simulations, which limits its application to real-world problems. The present study aimed at obtaining a general-purpose quantitative structure-kinetics re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We report that selected RF-Score-based descriptors for HSP90 and p38 MAP kinase subsets perform better than the reference models based on molecular descriptors, reported previously to correlate with binding kinetics and SIFP fingerprints. Similarly, Su et al reported a higher correlation for extended RF-Score descriptors over molecular descriptors for the HSP90 set, starting with robust dataset preparation. The research in the direction of high-throughput methods for binding kinetics is currently being continued.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We report that selected RF-Score-based descriptors for HSP90 and p38 MAP kinase subsets perform better than the reference models based on molecular descriptors, reported previously to correlate with binding kinetics and SIFP fingerprints. Similarly, Su et al reported a higher correlation for extended RF-Score descriptors over molecular descriptors for the HSP90 set, starting with robust dataset preparation. The research in the direction of high-throughput methods for binding kinetics is currently being continued.…”
Section: Discussionmentioning
confidence: 91%
“…We assume that the significant difference in the test set results is partly due to the fact that our models were tested on external test sets with various protein structures. It should be noted that a highly similar random forest approach had recently been applied in Su’s work for binding kinetics predictions. The authors curated a database composed of 406 protein–ligand complexes with k off data and constructed ML models based on the extended RF-score descriptors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Su et al adopted distance-dependent protein−ligand atom pair descriptors and a random forest algorithm to derive a quantitative structure−kinetics relationship model for predicting the dissociation rate constant of a ligand. 18 In this work, neural network (NN) models are developed to predict the temperature-dependent rate constants of the title reactions with the molecular structure descriptors as input. Particular attention is paid to predicting the site-specific rate constants.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Goldsmith utilized a machine learning surrogate potential energy surface to replace the direct CASPT2 energy in variational transition state calculations, by which the computational costs were greatly reduced . Su et al adopted distance-dependent protein–ligand atom pair descriptors and a random forest algorithm to derive a quantitative structure–kinetics relationship model for predicting the dissociation rate constant of a ligand …”
Section: Introductionmentioning
confidence: 99%